Online Review Management in Hotel Industry - Nguyen, Kim (My University, 2015)
The impact of online reviews and social media on hotel business has reached an unprecedented level, given the vast amount of people checking posted opinions prior to making their booking decisions. This study, thus, aims to provide insight into a complete online review management (ORM) strategy. In order to find out the guidelines for managing reviews, both secondary and primary data were collected. Based on secondary data, two frameworks were created. Framework 1 explains the role of online reviews on hotel business and consumption, Framework 2 presents the ORM guidelines. The primary data collection consisted of interviews with five (5) hotels that are diverse in types, sizes and locations. Those hotels were chosen as they are shown to be practicing ORM. The purpose was to understand how hoteliers carry out ORM in reality. The interview questions and findings analysis were based on the created frameworks. The results show that ORM guidelines include five efforts in order: (1) creating a remarkable guest experience, (2) encouraging online reviews, (3) monitoring online reviews, (4) responding to online reviews, and (5) acting upon attained information.
Keywords: Online Reviews; Online Review Management; User-generated Content; Word-of-mouth; eWord-of-mouth; Social Media; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|